(untitled) (Bangladesh Critical Care Journal, 2026)
Background: Critical illness is characterized by a loss of commensal flora and an overgrowth of potentially pathogenic bacteria, leading to a high susceptibility to infection. Ventilator associated pneumonia (VAP) remains a common hazardous complication in patients who are mechanically ventilated and associated with increased cost, adverse outcome. The use of probiotics has been accepted as a strategy to prevent VAP offering a effective combination of safety, simplicity and cost-effectiveness. Objective: To evaluate the role of probiotics in reducing the incidence VAP in neuro-critical care patients who received mechanical ventilation for at least 48 hours. Methodology: This randomized controlled trial was conducted in the ICU of Dhaka Medical College Hospital at Department of Anaesthesia, Pain, Palliative & Intensive Care over a period of 20 months without interrupting standard care practiced in the department. A total of 135 neuro-critical patients admitted in ICU, who needful mechanical ventilation for at least 48 hours were enumerated qualified for inclusion. Participants were randomly allocated into two groups using a simple lottery method in a 1:1 ratio. The intervention group received probiotic supplementation and control group received placebo. The Clinical Pulmonary Infection Score (CPIS) criteria was used for diagnosis of VAP in all patients. Data were analyzed using SPSS version 26.0 with statistically significant p-value <0.05. Results: The mean ± SD age of patients in the intervention group was 41.1 ± 11.86 years and in the control group was 43.2 ± 9.92 years, without any significant difference between groups (p>0.05). There was no statistically significant difference in baseline characteristics including age, sex, comorbidities and smoking status. The incidence of VAP was significantly lower in the intervention group compared to the control group (5.7% vs 25.3% , p= 0.002). Conclusion: Probiotic administration was associated with a significant reduction in the incidence of ventilator associated pneumonia in the neurocritical patients. Bangladesh Crit Care J March 2026; 14 (1): 11-15